Consumers’ Organic Food Purchase Behavior in Bangladesh : An Extended Theory of Planned Behavior Approach - Shanta, Shamima Easmin; Julhaz Hossain, Md.; Biswas, Rumana; Abdul Alim, Md.; Anjuman Ara, Mst. (Indian Journal of Marketing, 2025)
Purpose : The current study examined consumers’ intention and actual purchase behavior to buy organic foods. An extended theory of planned behavior was utilized to minimize the deficiency in this area of literature. Design/Methodology/Approach : A quantitative online survey was conducted using the purposive sampling technique, and a total of 442 organic food consumers were recruited from Bangladesh. The collected data were estimated employing partial least squares-structural equation modeling (PLS-SEM) to test the hypothesized relations. Findings : The findings depicted that product availability, attitude, health consciousness, and consumer trust greatly influenced consumers’ organic food purchase intention and, in turn, their actual purchase behavior. The estimations further confirmed that consumer trust played a significant role in mediating the relationships between product information and consumers’ organic food purchase intention. Practical Implications : This study offered valuable insights for decision-makers, organic food marketers, academics, and practitioners, focusing on organic food availability, grasping consumer attitudes, catering to health-conscious consumers’ needs, and boosting their trust. Originality : Unlike earlier investigations, this study extends the theory of planned behavior approach by crafting a contributory framework to examine consumers’ actual purchase behavior toward organic foods.